INCREASING OF ECOLOGICAL SAFETY OF THE PROCESSES OF SILUMINS REFINING DUE TO APPLICATION OF LOW-TOXIC FLUX METALS AND PREPARATIONS - G. A. Rumjantseva; B. M. Nemenenok; S. P. Zadrutskij; A. M. Muravitskij (Литьë и металлургия, 2010)
It is shown that the received complex of mechanical and technological characteristics of alloy AK9 after processing of melt with investigated fluxes and preparations can be recommer ded for use in plant conditions that will enable the increase of ecological safety of color-founding production.